2017
DOI: 10.1088/1757-899x/254/4/042004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of flax roving composites reinforcement

Abstract: The mechanical properties of flax and hemp fibres reinforced geopolymer composites K Korniejenko, M ach, M HebdowskaKrupa et al.Destruction of concrete beams with metal and composite reinforcement under impulse action A V Radchenko, P A Radchenko, S P Batuev et al. AbstractThe work consists of analyzing three roving linen of different linear density (200 tex, 400 tex, 2000 tex) and three fabrics (satin, twill weave and plain weave) which were made on rapiere loom called Picanol. The purpose of the study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Due to the low density and cell structure of natural fi bers, these composites have very good acoustic and thermal insulation properties. Natural fi bers are especially recommended in cases where it is important to reduce production costs and where it can compete with artifi cial glass fi bers (E-glass fi ber), where high stiffness per unit mass is desired [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low density and cell structure of natural fi bers, these composites have very good acoustic and thermal insulation properties. Natural fi bers are especially recommended in cases where it is important to reduce production costs and where it can compete with artifi cial glass fi bers (E-glass fi ber), where high stiffness per unit mass is desired [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Textile composites are formed to use textile fi bers, yarns, and fabrics as a composite reinforcement to achieve high-strength and lowdensity composites with reasonable manufacturing cost [4,5,6]. Nowadays, fl ax fi ber-reinforced composite is one from natural fi ber textile-reinforced composites, which is getting more attention from manufacturing industries and researchers due to its unique properties, including cost-effectiveness, low density, good specifi c strength, good bio-degradability, and environment-friendly material [3,5,[7][8][9][10]. These properties widely spread the usage of fl ax fi ber-reinforced composites in the aerospace, civil engineering, automotive, and many other industries [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Prasad et al [17] showed the infl uence of composite preparation methods on the mechanical strength of composite material. Many researchers investigated and revealed that UD composites provide the greatest strength in the fi ber direction [7,9,12].…”
Section: Introductionmentioning
confidence: 99%